2019
DOI: 10.1371/journal.pgen.1008393
|View full text |Cite
|
Sign up to set email alerts
|

The type IV pilus protein PilU functions as a PilT-dependent retraction ATPase

Abstract: Type IV pili are dynamic cell surface appendages found throughout the bacteria. The ability of these structures to undergo repetitive cycles of extension and retraction underpins their crucial roles in adhesion, motility and natural competence for transformation. In the beststudied systems a dedicated retraction ATPase PilT powers pilus retraction. Curiously, a second presumed retraction ATPase PilU is often encoded immediately downstream of pilT. However, despite the presence of two potential retraction ATPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 81 publications
8
46
0
Order By: Relevance
“…Our results indicate that PilU can only facilitate pilus retraction in the presence of PilT, regardless of whether that PilT is a functional ATPase. These results are also supported by a recent report from the Blokesch lab, which was published while our manuscript was in revision [41]. We initially tested the hypothesis that this was due to a requirement for PilT to bridge PilU with the platform protein PilC.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results indicate that PilU can only facilitate pilus retraction in the presence of PilT, regardless of whether that PilT is a functional ATPase. These results are also supported by a recent report from the Blokesch lab, which was published while our manuscript was in revision [41]. We initially tested the hypothesis that this was due to a requirement for PilT to bridge PilU with the platform protein PilC.…”
Section: Discussionsupporting
confidence: 81%
“…cholerae competence pili ( Fig 1A and S1 Fig ). Additionally, it was very recently shown that PilU from Pseudomonas aeruginosa can also promote retraction in a PilT-dependent manner [41]. Together, these results demonstrate that PilU ATPase activity facilitates pilus retraction in a PilT-dependent manner in at least three gammaproteobacteria ( V .…”
Section: Resultsmentioning
confidence: 66%
“…6), suggesting that PilU can only function as a retraction ATPase for the MSHA system in the presence of PilT. Similar results have recently been reported for MSHA and ChiRP pili for O1 El Tor strain A1552, as well as for ChiRP in strain E7946, suggesting that this PilT-dependent PilU function is similarly conserved across O1 El Tor isolates 37,38 . c-di-GMP levels mediate MSHA production and retraction.…”
Section: Msha Retraction Appears Common Among O1 El Tor Isolatessupporting
confidence: 80%
“…Our analysis confirms that PilU is indeed not needed for retraction but does affect retraction speed (Supplementary Figure 6). Recent studies also suggest that these motors may have more complicated interactions 38,39 , and in the future our model could help tease apart the specific contributions of different mutants to the extension and retraction cycle.…”
Section: Discussionmentioning
confidence: 87%